The Cowpea Kinome: Genomic and Transcriptomic Analysis Under Biotic and Abiotic Stresses - Ferreira-Neto, José Ribamar Costa; Borges, Artemisa Nazaré da Costa; da Silva, Manassés Daniel; Morais, David Anderson de Lima; Bezerra-Neto, João Pacífico; Bourque, Guillaume; Kido, Ederson Akio; Benko-Iseppon, Ana Maria (Frontiers in Plant Science, 2021)
The present work represents a pioneering effort, being the first to analyze genomic and transcriptomic data from Vigna unguiculata (cowpea) kinases. We evaluated the cowpea kinome considering its genome-wide distribution and structural characteristics (at gene and protein levels), sequence evolution, conservation among Viridiplantae species, and gene expression in three cowpea genotypes under different stress situations, including biotic (injury followed by virus inoculation – CABMV or CPSMV) and abiotic (root dehydration). Structural features of cowpea kinases (VuPKs) indicated that 1293 bona fide VuPKs covered 20 groups and 118 different families. The RLK-Pelle was the largest group, with 908 members. Insights on the mechanisms of VuPKs genomic expansion and conservation among Viridiplantae species indicated dispersed and tandem duplications as major forces for VuPKs distribution pattern and high orthology indexes and synteny with other legume species, respectively. Ka/Ks ratios showed that almost all (91%) of the tandem duplication events were under purifying selection. Candidate cis-regulatory elements (CCREs) were associated with different transcription factors (TFs) in promoters regions of the RLK-Pelle group. C2H2 TFs were closely associated with the promoter regions of almost all scrutinized families for the mentioned group. At the transcriptional level, it was suggested that VuPKs up-regulation was stress-, genotype-, or tissue-dependent (or a combination of them). The most prominent families in responding (up-regulation) to the all analyzed stresses were RLK-Pelle_DLSV and CAMK_CAMKL-CHK1. Concerning root dehydration, it was suggested that the up-regulated VuPKs are associated with ABA hormone signaling, auxin hormone transport and potassium ion metabolism. Additionally, up-regulated VuPKs under root dehydration potentially assist in a critical physiological strategy of the studied cowpea genotype in this assay, with activation of defense mechanisms against biotic stress while responding to root dehydration. This study provides the foundation for further studies on the evolution and molecular function of VuPKs.